Microsporogênese comparativa entre Brachiaria ruziziensis (R. Germ & Evrard) diploide, tetraploide e suas progênies - Morais, Ludmila Caproni (2017)
Studies on the microsporogenesis in Brachiaria have focused on B. ruziziensis, B. decumbens and B. brizantha species, and their interspecific hybrids for being especially important as fodder plants. Besides its sexual behavior, B. ruziziensis is among a minority of diploid species in Brachiaria (2n = 2x = 18), while most species of this genus are tetraploid (2n = 4x = 36) and apomictic. B. ruziziensis is used in intra and interspecific crosses. The success of interspecific hybridization depends on the artificial tetraploidization in B. ruziziensis and on the hybrids, both intra and interspecific crosses, that must present regular meiosis and high rate of pollen viability. Based on that, the aim of this work was to compare the microsporogenesis process in diploid and tetraploid individuals of B. ruziziensis, which were used as female genitors in breeding and their respective progenies. Analyses were conduct using plant material provided by EMBRAPA Dairy Cattle, from which inflorescences were sampled, fixed in an absolute ethyl alcohol: acetic acid: propionic acid solution (6:3:2) and stored at -4°C. Squash technique using 1% propionic carmine was used for meiotic analyses. For pollen viability, analyses consisted on Alexander’s stain. Abnormalities were found throughout the meiotic process in diploid and tretraploid families, but in general, rate of abnormalities was considered low, with percentage varying according to the genotype analyzed. The diploid family was considered more stable. Diploid and tetraploid progenies and their respective mother plant showed similar rate of meiotic abnormalities, what suggests that genetic combinations used in crosses or self-fertilization were stable. For diploid accesses pollen viability was high, reaching up to 88.3%. On the other hand, tetraploid individuals showed lower rates, with a maximum of 61.1%.